2020
DOI: 10.14738/assrj.75.8298
|View full text |Cite
|
Sign up to set email alerts
|

A State of De-Stress: Examining the Relationship Between Subjective Well-Being, Self-Compassion, and Empathy

Abstract: University can be a period of stress caused by academic, social, or personal demands. Yet most are able to rise above the adversity and grow from their experiences. Research on stress has found that a negative association exists with subjective well-being broadly conceptualized as life happiness (Denovan & Macaskill, 2017; Zhang, 2009). There are also positive relationships demonstrated between self-compassion and empathy with subjective well-being (Bluth et al., 2016; Thomas et al., 2007). This study exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 33 publications
1
9
0
5
Order By: Relevance
“…Researchers specifically examined the relationship between these two variables for fresh graduates who have not worked in Jakarta. Previous research conducted in Canada [7] found a relationship between stress and subjective well-being and this relationship was moderated by self-compassion. This means that these findings are in line with what researchers have done, that the higher a person's self-compassion, the higher the subjective well-being of the individual, where the stress condition assumed by researchers here is that the condition is not working or unemployed.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Researchers specifically examined the relationship between these two variables for fresh graduates who have not worked in Jakarta. Previous research conducted in Canada [7] found a relationship between stress and subjective well-being and this relationship was moderated by self-compassion. This means that these findings are in line with what researchers have done, that the higher a person's self-compassion, the higher the subjective well-being of the individual, where the stress condition assumed by researchers here is that the condition is not working or unemployed.…”
Section: Discussionmentioning
confidence: 77%
“…In South Jakarta, a scholar also committed suicide by stabbing a kitchen knife into his neck because of the stress of being unemployed for too long [19]. Based on the results of previous research in Canada (Hablado & Clark, 2020), it was found that there was a relationship between stress and subjective well-being and this relationship was moderated by self-compassion. The results of other research conducted by Ratnasari and Sumiati [17] show that four dimensions, namely self-compassion, religiosity, support group affiliation and income have a significant effect on subjective well-being in parents who have children with mental retardation.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies show that self-compassion is positively related to social ties. The compassion we direct to ourselves is the one we offer to other people (18,44) . The connection with the other's suffering drives the group to a loving dialog with the other or with oneself and allows practical reflections for more resilient states (18) .…”
Section: Discussionmentioning
confidence: 99%
“…A autocompaixão aumentou ao longo do tempo para as pessoas participantes da intervenção. Esse aumento A compaixão que direcionamos a nós mesmos é a que damos às outras pessoas (18,44) . A conexão com o sofrimento do/a outro/a impulsiona o grupo ao diálogo amoroso com o/a outro/a ou consigo e permite reflexões práticas para estados mais resilientes (18) .…”
Section: Autocompaixão E Consciência Dos Estados Mentais Para O Ativ...unclassified
“…Em relação ao tempo, notou-se uma redução do início para o término do curso e aumento no período entre o fim e após três meses de intervenção. O aumento do bem-estar subjetivo em longo prazo foi relatado e associado ao autocuidado, à autocompaixão e à empatia conforme sugerem estudos (10,44) . O propósito da prática não é aumentar afetos positivos ou reduzir negativos, e sim viver o presente, indo ao encontro da sensação que surge sem criar apego ou aversão e percebendo a experiência como ela é. Estudos em populações socialmente vulneráveis mostram melhora na regulação emocional e na relação social (23,45) .…”
Section: Autocompaixão E Consciência Dos Estados Mentais Para O Ativ...unclassified